Impact of Job Design on Employees Psychological Work Reactions (Job Satisfaction &Turnover Intentions, Organizational Commitment & Organizational Citizenship Behavior): Empirical Evidence from the Universities of Khyber Pakhtunkhwa - ADIL KHAN (Journal of Business & Tourism, 2021)
This study explores the effect of job design on employees psychological work reactions i.e. (job satisfaction and commitment) on employee’s organizational citizenship behavior (OCB) of public sector universities of Khyber Pakhtunkhwa (KP), Pakistan. The objective of the study was to measure the effect of job characteristics on OCB, satisfaction and commitment and regression analysis predicts that a job characteristic was found as a significant predictor of OCB, job satisfaction and job commitment in public sector employee. Result of the study revealed that job characteristic is a significant predictor of OCB, job commitment and job satisfaction. Recommendation and suggestions are also included in the study.